A new strategy to integrate Heath-Carter Somatotype Assessment with bioelectrical impedance analysis in elite soccer players - Campa, F.; Bongiovanni, T.; Matias, C. N.; Genovesi, F.; Trecroci, A.; Rossi, A.; Iaia, F. M.; Alberti, G.; Pasta, G.; Toselli, S. (Sports, 2020)
Easy-to-apply and quick methods for evaluate body composition are often preferred when assessing soccer teams. This study aimed to develop new equations for the somatotype quantification that would reduce the anthropometric measurements required by the Heath and Carter method, integrating the somatotype assessment to the bioelectrical impedance analysis (BIA). One hundred and seventy-six male elite soccer players (age 26.9 ± 4.5 years), registered in the Italian first division (Serie A), underwent anthropometric measurements and BIA. Endomorphy, mesomorphy, and ectomorphy were obtained according to the Heath and Carter method, while fat mass (FM) and fat free mass (FFM) estimated using a BIA-derived equation specific for athletes. The participants were randomly split into development (n = 117) and validation groups (n = 59, 1/3 of sample). The developed models including resistance2/stature, FM%, FFM, contracted arm and calf circumference, triceps, and supraspinal skinfolds had high predictive ability for endomorphy (R2 = 0.83, Standard Error of Estimate (SEE) = 0.16) mesomorphy (R2 = 0.80, SEE = 0.36), and ectomorphy (endomorphy (R2 = 0.87, SEE = 0.22). Cross validation revealed R2 of 0.80, 0.84, 0.87 for endomorphy, mesomorphy, and ectomorphy, respectively. The proposed strategy allows the integration of somatotype assessment to BIA in soccer players, reducing the number of instruments and measurements required by the Heath and Carter approach.